Edukasi Si Gulatus: Siaga Gula dan Lawan Ancaman Diabetes Melitus - Firmansyah Firmansyah; Amanda Khaerani Salsabella; Alya Nida Tendyansyah (BALE LITERASI, 2026)
Diabetes Mellitus (DM) is a chronic disease caused by insulin hormone disruption, which is closely related to lifestyle and dietary habits. Health education is highly necessary to increase knowledge that serves as a foundation for altering patients' daily behaviors. This community service utilized education and capacity-building methods through the